Impacts of sheep versus cattle livestock systems on birds of Mediterranean grasslands - Rita F. Ramos (Nature Portfolio, 2021)
Abstract Mediterranean pastures are experiencing strong changes in management, involving shifts from sheep to cattle-based livestock systems. The impacts of such shifts on biodiversity are still poorly understood. Here, we sought to contrast the grazing regime, vegetation structure, bird species richness and abundance, between sheep and cattle grazed parcels, to understand the mechanisms through which management decisions impact farmland birds. During spring 2019, we characterized livestock management, bird populations and sward structure in 23 cattle and 27 sheep grazed parcels. We used a Structural Equation Model to infer the direct and indirect effects of sheep and cattle grazing on birds. Although no effects were found on overall species richness, there were species-specific responses to sheep and cattle grazed systems. Grazing pressure (variable integrating stocking rate and the number of days in the parcel) had negative impacts on the prevalence/abundance of Zitting Cisticola, Corn Bunting and Little Bustard, either directly or indirectly, through the effects of grazing pressure on vegetation height. Animal density and vegetation cover had direct positive effects in Galerida spp. and Common Quail, respectively. Zitting Cisticola and Little Bustard also showed a direct response to livestock type. Our study emphasizes the importance of grazing pressure as a driver of negative impacts for bird populations in Mediterranean grasslands. Since the ongoing transition from sheep to cattle-based systems involves increases in stocking rate, and therefore potentially higher grazing pressure, we propose a policy change to cap the maximum allowed grazing pressure. At the landscape scale, a mix of sheep and cattle grazed fields would be beneficial for maintaining bird diversity.